Characterization of immune microenvironment infiltration and m6A regulator-mediated RNA methylation modification patterns in osteoarthritis - Ouyang, Yulong; Tu, Yuanqing; Chen, Shuilin; Min, Huan; Wen, Zhexu; Zheng, Guihao; Wan, Ting; Fan, Hao; Yang, Wenzhao; Sun, Guicai (Frontiers in Immunology, 2022)
Background: Few studies have been reported the potential role of N6-methyladenosine (m6A) modification in osteoarthritis (OA). We investigated the patterns of m6A modification in the immune microenvironment of OA. Methods: We evaluated the m6A modification patterns based on 22 m6A regulators in 139 OA samples and systematically associated these modification patterns with immune cell infiltration characteristics. The function of m6A phenotype-related differentially expressed genes (DEGs) was investigated using gene enrichment analysis. An m6A score model was constructed using principal component analysis (PCA), and an OA prediction model was established based on the key m6A regulators. Results: Healthy and OA samples showed significant differences in the expression of m6A regulators. Nine key m6A regulators, two m6A modification patterns, m6A-related genes and two gene clusters were identified. Some m6A regulators had a strong correlation with each other. Gene clusters and m6A clusters have high similarity, and cluster A corresponds to a high m6A score. Immunocytes infiltration differed significantly between the two clusters, with the m6A cluster B and gene cluster B having more types of infiltrating immunocytes than cluster A. The predictive model can also predict the progression of OA through m6A regulators expression. Conclusions: Our study reveals for the first time the potential regulatory mechanism of m6A modification in the immune microenvironment of OA. This study also sheds new light on the pathogenesis of OA.